Barriers in the transition from research and development to commercialization of nanotechnology in Malaysia / Kasthoory Rajalingam - Kasthoory , Rajalingam (2015)
Malaysia has exhibited a profound interest, thus far lacking in the developmental concentration in the field of nanotechnology since the embryonic formation of the National Nanotechnology Initiative (NNI) in 2006. There have been evident barriers, which disconnect the and commercialization of this technology from spanning through a progressing and transcending flow of innovative efficiency. This thesis aims to: (i) To identify the critical barriers that constrain the R&D and commercialization of nanotechnology in Malaysia, and (ii) To provide recommendations for policy actions and future studies for nanotechnology R&D and commercialisation in Malaysia. This thesis illustratively explains the author’s design of various factors, distinctively developed through a series of time series - citation analyses of core referred journals from 1989 – 2014 (26 year period). Citation analyses were conducted manually since the main element embedded within the core subject theme of each paper was not explicitly detected through title headings by use of any software. Graphical mappings were designed to prove the existence of missing gaps in literature and how it was relevant to the construction of a conceptual framework and its associated building blocks. Missing gaps were identified in the area of: I: The hybrid of comprehensive vs non-comprehensive education of nanotechnology II: The distinct priorities of academia and industry and how it affects the R&D and commercialization of nanotechnology III: The formation of R&D policy for nanotechnology This thesis explains the conceptual framework design through the formation of building blocks functioning as individual units of structure composed to formulate a larger subject entity that interoperate with interdependent units found within the structural assemblage. This thesis also provides an explicit presentation of exploratory questions designed to guide the qualitative research study - design model. Sampling method via purposive sampling and triangulation have been explained in terms of reason, sampling size and methodology. The findings establish that university researchers and students are undeniably the knowledge bearing assets required during the invention or discovery stage and prototyping or testing stage from R&D to the commercialization of nanotechnology. This thesis proves that there is an absolute need for a skilled and educated workforce trained within an array of levels bifurcating from nanotechnology to congregate the projected demand in the future. Apart from human capital and technological capability, aspects such as infrastructure and capital investment also come into play in the pursuit towards realising a solid bridge between R&D and commercialization of nanotechnology. Considering that a lot of investments have been made in the area of science and technology, although not specifically in the area of nanotechnology development and not many significant results attained, the main implication of this study is that it unveils the key anomalies existing within the nanotechnology environment to give the government and policy makers reason to invest in developing solutions to prevent the occurance of bottlenecks. The main findings and recommendations indicate the urgency to prepare human capital in nanotechnology through education and training for the fulfilment of nanotechnology relevant research activities in the next ten years. Besides, it is crucial to make known the total cost of key infrastructure required to undertake a nanotechnology research activity in preparation for financial apportionments by potential applicants, the parallel importance of patents and publications in universities, and its role in sustaining nanotechnology research. Furthermore, this thesis suggests that the needs in adopting a multidisciplinary approach in nanotechnology educational programme and the potential roles that can be played by the Malaysian government to assist universities in creating research opportunities in nanotechnology through University-Industry partnerships.